2015
DOI: 10.3348/kjr.2015.16.4.723
|View full text |Cite
|
Sign up to set email alerts
|

Stent Compression in Iliac Vein Compression Syndrome Associated with Acute Ilio-Femoral Deep Vein Thrombosis

Abstract: ObjectiveThis study was conducted to evaluate stent compression in iliac vein compression syndrome (IVCS) and to identify its association with stent patency.Materials and MethodsBetween May 2005 and June 2014, after stent placement for the treatment of IVCS with acute ilio-femoral deep vein thrombosis, follow-up CT venography was performed in 48 patients (35 women, 13 men; age range 23-87 years; median age 56 years). Using follow-up CT venography, the degree of the stent compression was calculated and used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…An approximately oval shape can be seen at these levels of high compression, but a residual stenosis of more than 50% would be unacceptable [25]. A study [18] found that the proportion of signi cant stent compression was 33%; 56% of patients in the signi cant stent compression group developed stent occlusion, while only 9% developed stent occlusion in the insigni cant group, indicating that signi cant compression of the nitinol stents obviously affects stent patency. Additionally, the diameter reduction caused by stent compression may result in venous hypertension and residual symptoms of lower extremity, although patency may be retained [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An approximately oval shape can be seen at these levels of high compression, but a residual stenosis of more than 50% would be unacceptable [25]. A study [18] found that the proportion of signi cant stent compression was 33%; 56% of patients in the signi cant stent compression group developed stent occlusion, while only 9% developed stent occlusion in the insigni cant group, indicating that signi cant compression of the nitinol stents obviously affects stent patency. Additionally, the diameter reduction caused by stent compression may result in venous hypertension and residual symptoms of lower extremity, although patency may be retained [19].…”
Section: Discussionmentioning
confidence: 99%
“…All the ultrasound images were reviewed by two different ultrasonologists, and two different radiologists reviewed the MDCTV examinations, all reviewers were blinded to the history of patients and other imaging results. The degree of stent compression was evaluated by calculating the percentage of diameter reduction of the patent lumen of the stent (diameter of the stent at the narrowest segment/diameter of the stent at the normal segment × 100%) [18]. The degree of stent compression was de ned as "signi cant" if the luminal collapse was 50% or more and as "insigni cant" if the luminal collapse was below 50%.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…All the ultrasound images were reviewed by two different ultrasonologists, and two different radiologists reviewed the MDCTV examinations, all reviewers were blinded to the history of patients and other imaging results. The degree of stent compression was evaluated by calculating the percentage of diameter reduction of the patent lumen of the stent (diameter of the stent at the narrowest segment/diameter of the stent at the normal segment × 100%) [ 17 ]. The degree of stent compression was defined as “significant” if the luminal collapse was 50% or more and as “insignificant” if the luminal collapse was below 50%.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these therapeutic benefits, stent dysfunctions such as stent compression and in-stent restenosis (ISR) are common complications [ 5 , 14 , 16 ]. Significant compression of nitinol stents highly affects stent patency [ 17 ], and it has been reported that approximately 20 percent of stents will require reintervention for ISR [ 18 ].…”
Section: Introductionmentioning
confidence: 99%